Socioeconomic risk moderates the association between caregiver cortisol levels and infant cortisol reactivity to emotion induction at 24 months. Issue 4 (28th February 2019) - Braren, Stephen H.; Perry, Rosemarie E.; Ursache, Alexandra; Blair, Clancy
Abstract: Relations between maternal baseline cortisol and infant cortisol reactivity to an emotion induction procedure at child ages 7, 15, and 24 months were analyzed using data from the Family Life Project ( N = 1, 292). The emotion induction consisted of a series of standardized and validated tasks, including an arm restraint, toy removal, and mask presentation, intended to elicit responses of fear and frustration. Results revealed that at 7 and 15 months, maternal baseline cortisol was negatively related to child cortisol reactivity, such that children of mothers with lower cortisol exhibited steeper cortisol increases in response to the emotion induction. At 24 months, the association between mother and infant cortisol was moderated by socioeconomic risk, such that maternal baseline cortisol was associated with child cortisol reactivity only in dyads characterized by low socioeconomic risk. Furthermore, at 24 months, children of mothers with low baseline cortisol and low socioeconomic risk exhibited decreasing cortisol responses, whereas children of mothers with low baseline cortisol but high risk exhibited flat cortisol responses. Children in dyads characterized by high baseline maternal cortisol also exhibited flat cortisol responses regardless of socioeconomic risk. The role of caregiver physiology in the regulation of the child's stress response in the context of adversity is discussed.